The effects of different surface contaminators on the shear bond strength of a universal adhesive system to dentin: an experimental study - Mahmoud Bahari; Siavash Savadi Oskoee; Mohammad Esmaeel Ebrahimi Chaharom; Nasim Molayi (Tabriz University of Medical Sciences, 2021)
Background. Contamination of dentin surface is one of the common problems in restorative dentistry. The aim was to investigate the effects of different surface contaminators on the dentin shear bond strength (SBS) of universal adhesive system (UAS) applied in etch-and-rinse (ER) and self-etch (SE) strategies. Methods. One hundred forty-four maxillary anterior sound human teeth were divided into six groups based on the types of surface contaminators: no surface contaminator (control) and experimental groups contaminated with blood, saliva, aluminium chloride (ALC), ferric sulphate (FS), and caries disclosing agent (CDA). Then, each group was further subdivided into two, based on the application strategy of UAS (ER and SE). After applying the adhesive according to the manufacturer's instructions, and bonding cylindrical composite samples, the SBS was measured. The data were analysed using two-way ANOVA, Tukey's HSD test and t test (P<0.05). Results. The SBS in all contaminated groups, except for CDA, was significantly lower in both ER and SE strategies compared to control group (P<0.05). A comparison between the application strategies revealed that ER and SE were only significantly different in the FS contaminated group (P<0.05). Conclusion. All tested contaminators, except CDA, significantly decreased SBS of UAS in both ER and SE strategies.